Language teaching and testing - a research of using literature forms in the English Language Schoolbooks - Jovanovska , Sashka (Indonesian Journal of Innovation Studies, 2019)
The use of literature forms in the English language teaching schoolbooks is enjoying a revival for a number of reasons. Having formed part of traditional language teaching approaches, literature became less popular when language teaching and learning started to focus on the functional use of language. However, the role of literature forms in the English language teaching schoolbooks has been re-assessed and many now view literary texts as providing rich linguistic input, effective stimuli for students to express themselves in other languages and a potential source of learner motivation. The aim of my thesis is to find out if in the English schoolbooks used in some schools set by experts. Although the studies on the use of literature forms in teaching English have been increasing abroad, in our country, particularly in public schools, only English grammar is being taught. The students who are expected to memorize these rules cannot use English. The aim of this seminar paper is to exhibit why and how literature forms can be used in order to teach English effectively and efficiently. I have also compared two schoolbooks (Project 2 and Dream team 3) to see the differences between the literary content.